Validation of Vehicle Drag Coefficient Performed by Using Simulation And Experimental Method - Rahman, Nik Asyar Farhanuddin Che; Nofrizalidris Darlis , (Progress in Engineering Application and Technology, 2024)
The drag coefficient is a common metric in automotive design, where designers strive to achieve a low coefficient. In the current work, minimising drag is done to improve fuel efficiency of vehicles without disturbing its performance and comfort to the passenger.  Current methodologies for assessing drag coefficients often rely on a combination of computational simulations and experimental testing. However, the potential disparities between simulated and experimental results raise concerns about the reliability of these assessments. The aim of this study involves the simulation of a vehicle model using Computational Fluid Dynamics (CFD) software and subsequent validation with experimental data obtained from a wind tunnel. The numerical analysis of flow over a geometry is performed using CFD software which is ANSYS Fluent while Aerolab Educational Wind Tunnel (EWT) will be used to get the experimental data. CFD is a branch of fluid mechanics that uses numerical methods with the help of computers to solve and analyse problems involving fluid flows. An overall percentage error below 10%, for drag coefficient is 2.2%, drag force is 4.2%, and Reynolds numbers is 1.5%. Generally considered acceptable in many engineering applications. The integration of simulation and experimental methods in validating vehicle drag coefficients represents a valuable approach.  By continually refining and validating simulation models, their effectiveness in predicting aerodynamic performance can be ensured, ultimately contributing to advancements in vehicle design, fuel efficiency, and overall sustainability.